ANALISIS KONTRIBUSI BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN (BPHTB) DAN PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN (PBB-P2) TERKAIT DENGAN PENDAPATAN ASLI DAERAH (PAD) PROVINSI DKI JAKARTA - Hj. Dewi Rejeki, SE., Ak., M.Ak. M.Si., CA.; Risky Defi Jayanti (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2018)
This research was conducted to determine the contribution of Land and Building Rights (BPHTB) and Land and Rural and Urban Building Taxes (PBB-P2) as well as from Land and Building Rights (BPHTB) Customs Taxes and Rural and Urban Land and Building Taxes. (PBB-P2) whichever is more contributing is related to the Original Regional Revenue of DKI Jakarta Province. This research was conducted at the DKI Jakarta Provincial Tax and Retribution Agency. This research is a qualitative descriptive study. Data taken from the Regional Original Revenue Report (PAD) in the form of target data and realization of Land and Building Rights (BPHTB) Acquisition and Land and Rural and Urban Building Taxes (PBB-P2) of DKI Jakarta Province 2013-2017. The analysis used was descriptive analysis using the ratio of the contribution of Land and Building Rights (BPHTB) and Land and Building Rural and Urban Taxes (PBB-P2). In addition, data is obtained through observation, interviews, and documentation. The results showed that the average percentage of revenue contribution given by Land and Building Rights (BPHTB) was related to the DKI Jakarta Province's Original Regional Revenue during the 2013 fiscal year up to 2017, which amounted to 12.26% with the